Effects of Taekwondo Training on Body Composition: A Systematic Review and Meta-Analysis - Seunghui Baek (MDPI AG, 2021)
Background: The purpose of this study is to investigate the effect of Taekwondo training on body composition and to evaluate the magnitude of the effect. Methods: Databases were used to select studies related to the effectiveness of Taekwondo training, and the inclusion criteria were as follows. Results: Thirty-seven studies were selected. We found statistically significant differences from the control group in weight, body mass index (BMI), waist circumference (WC), waist–hip ratio (WHR), body fat mass, body fat percentage, lean mass, and muscle mass. Also, the age group was statistically significant in control variables on weight, BMI, and body fat percentage. Conclusions: Taekwondo training had a positive effect on body composition, and these results suggest that Taekwondo training is an effective exercise method to lower obesity.